EFFECT OF ACUTE EXPOSURE OF GLYPHOSATE HERBICIDE, ON WISTAR RATS WITH REFERENCE TO HAEMATOLOGY AND BIOCHEMICAL ANALYSIS - U. S. DESHMUKH,; FAIZA IRAM,; M. S. JOSHI, (The Bioscan, 2013)
Herbicides have been used tremendously worldwide to control the unwanted herbs or weeds. Herbicides are synthetic compounds having the ability to inhibit the growth of plant or to kill it. Directly or indirectly these herbicides enters to our body, through accumulated in fruits, grains and water, or accidentally. Rats were exposed to oral dose of LD 50 of Glyphosate for 7 days (4000 mg/kg body weight) to study haematological and biochemical alterations, it shows that Roundup interferes with blood components altering their basic composition, Significant increase in RBC count, significant decrease in the Hb% and TLC also causing alterations in metabolism, significant increase were found in alkaline phosphatase, total proteins, glucose etc.